Nigeria: Hungry Nation in a Land of Plenty - Philip Fwaldin Kasuwa (Przegląd Prawno-Ekonomiczny)
Hunger is a pressing global concern. The prevalence of undernourishment, a crucial measure of hunger, is a global challenge. Many factors are responsible including poverty, political instability, economic disparities, climate change, and conflicts. The global nature of hunger underscores the urgency and collective responsibility to address this issue, demanding immediate action from all of us. Often heralded as a land of vast agricultural potential and rich natural and human resources, Nigeria faces a paradoxical struggle with pervasive hunger and food insecurity. This article explores Nigeria’s multifaceted hunger crisis despite its capacity to be a leading food producer in Africa. We examine the socio-economic and political dynamics that contribute to this disparity, including issues such as land distribution inequities and the impact of oil dependency. Additionally, the article analyses the role of government policies and infrastructure deficits. The goal of this work is to 1) analyse the concept of national wealth and its implications for economic development, 2) investigate the factors contributing to hunger and food insecurity in Nigeria despite its abundant resources, 3) provide insights and recommendations for addressing the country’s wealth inequality and hunger challenges, and 4) contribute to the academic understanding of the complex relationship between wealth, poverty, and development in nations.